Byzantine Agreement Service for Cooperative Wireless Embedded Systems - Xu, Wenbo; Wegner, Martin; Wolf, Lars; Kapitza, Rüdiger (Proceedings - 47th Annual IEEE/IFIP International Conference on Dependable Systems and Networks Workshops, DSN-W 2017, 2017)
Recently there is a number of scenarios such as vehicle platooning, UAV swarms and cooperative robots, where a group of autonomous entities needs to make joint decisions to operate effectively. Distributed agreement protocols can play a key role to establish a common view on context parameters and to coordinate joint actions. Due to the harsh environmental conditions in some of these scenarios and their safety critical nature such protocols need to tolerate arbitrary faults and even malicious attacks.This paper presents a framework for Byzantine fault tolerant agreement for small-sized groups of autonomous, wirelessly connected systems. It focuses, besides providing support for general purpose value agreement, on the agreement of distributed sensor readings. The latter enables to establish a joint view on context conditions, thereby building the basis for joint coordinated actions. As classical Byzantine fault tolerant agreement protocols require 3t + 1 participants to tolerate t faulty nodes, we also consider a hybrid fault model by utilizing a trusted subsystem, which can only be subject to crashes. The latter reduces the required group size for agreement to 2t + 1 nodes and reduces the message complexity of the protocol, which is essential for the targeted scenarios. The experiment results show that the trusted subsystem can effectively increase the efficiency.
CRIS-Team Scopus Importer:2022-07-19
Keywords: Byzantine fault tolerance; distributed agreement; wireless embedded system